PREDICTIVE ASSESSMENT OF THE IMPACT OF CLIMATE CHANGE ON SUNFLOWER PRODUCTION: ANALYSIS OF DYNAMIC SERIES AND MODELING OF TRENDS - HUZ, MYKHAILO; CHUKHLIB, ALLA; SYMONENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Sunflower production serves as an example of the close interaction between climate changes and the cultivation of technical crops, the replacement of cultivation of other crops with the cultivation of sunflower, taking into account such characteristics as its thermophilic nature, which in conditions of increased temperatures and drought makes it possible to maintain productivity. The conducted research indicates significant changes in the dynamics of production and yield of sunflower, in particular in connection with climate change and differences in weather conditions, which affect production and yield in different regions of Ukraine. The author singles out several periods in the growth of the sunflower market in terms of production and yield from 2008 to 2013 - a period of stability; slight declines in production and yield in 2009 and 2012; 2014 – a significant drop in production volumes and yields; 2015-2016 - the recovery period; 2017, 2020 and 2022 are periods of significant decline in production due to economic dynamics, the pandemic and the war in Ukraine; 2018-2019 and 2021 - growth in cultivation and harvest. The evaluation of the series of dynamics in the gross harvest of sunflower in Ukraine demonstrates a significant dependence of its production and yield on the external environment and market conditions. We will use a polynomial function of arbitrary order to model and forecast sunflower production and yield. Constructed polynomial trend models of sunflower production and yield with a high degree of reliability reflect the real dynamics of indicators and demonstrate both an accelerated reduction in certain periods of time in the production and yield of the crop, and growth in periods of economic recovery. The forecast of production volumes and yields of sunflower for 2023-2025 indicates stability in the dynamics of these indicators in the medium term.